Geopolitics of the Balkans: 2019-2021 - Slobodan Janković (The Review of International Affairs, 2021)
Geopolitical analysis of the policies of the great powers over and in the Balkans in the period of three years is the object of this paper. The author initiates by retelling an event in 2019, indicative of one of the two theses of the text, namely that the US has returned to the Balkans. The second is the assumption, originally launched by the Russian geopolitician Dugin, that the Balkans are one of two monitors of world politics. The text is divided into five chapters. In the introductory part, the author defines his hypothesis and opts for Italian neoclassical geopolitical thought as a theoretical framework. The second chapter overviews basic socio-historical and geographical features of the Peninsula relevant for geopolitical understanding, while the third part of the text puts local political action of both external and internal actors into a broader geopolitical context. The fourth part is the most extensive and represents an overview of the most significant political actions of the great powers - Russia, the United States and China, and Germany, Turkey, and local countries. The conclusive part answers positively to Dugin’s assumption and confirms the thesis that great powers’ politics in the Balkans has regained importance for the US.